2009
DOI: 10.1016/s1015-9584(09)60395-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes and Prognostic Factors for T4 Gastric Cancers

Abstract: In patients with T4 gastric carcinoma, an aggressive surgical approach can be beneficial when curative resection is performed. If curative resection is not possible, palliative resection can be performed for a better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
3
26
0
2
Order By: Relevance
“…Survival in patients who underwent MVR without a complete resection was demonstrated to be significantly diminished compared to those who had an R0 resection [2,9,11,18]. Poor outcomes appear to be associated with both microscopic and macroscopic positive margins [12,15]. There were no 5-year survivors in three studies that reported outcomes in patients undergoing MVR with residual tumor; however, for patients in whom an R0 resection was achieved, the 5-year survival was 11.1-45.0% [2,9,18].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Survival in patients who underwent MVR without a complete resection was demonstrated to be significantly diminished compared to those who had an R0 resection [2,9,11,18]. Poor outcomes appear to be associated with both microscopic and macroscopic positive margins [12,15]. There were no 5-year survivors in three studies that reported outcomes in patients undergoing MVR with residual tumor; however, for patients in whom an R0 resection was achieved, the 5-year survival was 11.1-45.0% [2,9,18].…”
Section: Discussionmentioning
confidence: 93%
“…After removal of duplicates and screening for relevant titles and abstracts, a total of 142 articles were submitted for a full-text review. Seventeen studies involving 1343 patients met our inclusion criteria and were included in this review [1,2,[4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20] (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…también sería importante evaluar la calidad de vida de los enfermos tratados sin resección y la posibilidad que ellos tienen para lograr un tratamiento paliativo de buena calidad. Varios estudios han evaluado las complicaciones y la mortalidad de la GE al analizar aquellos enfermos tratados con una resección multi-orgánica y/o disección ganglionar extendida [6][7][8][9][10][11][12][13] . con el objetivo de obtener factores pronósticos de complicaciones postoperatorias y mortalidad, Viste y cols 17 evaluaron los resultados quirúrgicos de 1.010 enfermos sometidos a una gastrectomía y observaron 28% de morbilidad y 6% de mortalidad.…”
Section: Resultsunclassified
“…Está claramente demostrado que cuando la enfermedad está localizada, el tratamiento de elección es la resección quirúrgica 5 . Estudios recientes han confirmado que esto también sería aplicable a aquellos pacientes con tumores localmente avanzados con infiltración de órganos adyacentes 6,7 . A pesar de esto, la invasión local sería otro factor de mal pronóstico, independiente del tratamiento quirúrgico radical R0 8 .…”
Section: Instituto Oncológicounclassified
“…At the same time our R1 and R2 resection rates are also high (13% and 5%). In literature, there are some other studies stating that R0 resection rates of locally advanced gastric tumors, not treated with neo-adjuvant chemotherapy, are low (28). But now, there is increasing evidence that neo-adjuvant chemotherapy potentially down-stages the tumor and therefore may improve the resectability rate with negative surgical margins (29,30).…”
Section: Discussionmentioning
confidence: 99%